TINDAK PIDANA KEKERASAN FISIK OLEH SUAMI TERHADAP ISTRI MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Rio Angger Prasetyo, (2021)
The birth of a household that is intact and harmonious is realized from a safe condition and is free from any form of violence and there is no discrimination within the household. Thus the dream of everyone in the household is the unity and harmony of a happy, safe, peaceful, and peaceful household which is realized based on self-control and the quality of behavior of everyone in the household. Violence against women is an act that is contrary to human values. The formation of laws that are in accordance with legal protection of human rights as a form of instrument that protects individual and community rights that are very relevant so that they are related to programs that protect women from criminal acts of domestic violence. Therefore, the authors are interested in researching what are the forms of domestic violence according to the Law on the Elimination of Domestic Violence and the application of material criminal law in criminal acts of physical violence in the household. The normative juridical research method using library data is the method taken by the author to conduct this research which is based on a literature study from primary, secondary and tertiary legal sources which are then analyzed and researched. The author also uses a case study approach to decision number 189/Pid.sus/2019/pn.pms. Judges have juridical and non-juridical considerations in implementing decisions and imposing criminal sanctions with confidence in the judge that the defendant committed a criminal act as stated in the elements of the crime he was charged with. The judge must consider the testimony of the witness, the testimony of the defendant as well as the evidence related to one another which is described in accordance with the elements of the article contained in the indictment and see that the elements accused by the defendant have been proven and the defendant receives punishment according to his actions and the truth. juridical matters revealed in the trial made the judge decide the crime in accordance with the sense of justice in the crime of sexual violence, the application of material law by the husband to the wife is in accordance with the formulation of the criminal act committed by the defendant. Keywords: Criminal Act, Physical Abuse, Household.